The gentlewoman's remembrance : Patriarchy, piety, and singlehood in early Stuart England - Stephens, Isaac (Book collections on Project MUSE., 2016)
A highly original and detailed study of an individual single woman in early modern England, based on a recently discovered spiritual autobiography authored by a never-married gentlewoman, Elizabeth Isham. Provides new perspective on women's writing, identity and status in the early modern period.